(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
In the context of rapid globalization and technological development, contemporary architecture faces a fundamental dilemma: how to preserve local identity while meeting global standards and sustainability requirements. The article examines the complex interaction between local architectural traditions and global trends, analyzing their impact on shaping the modern architectural environment. The paper explores historical aspects of this interaction, the transformation of architectural styles under the influence of globalization processes, and the challenges associated with the threat of losing cultural authenticity. Special attention is paid to the phenomenon of "hybrid architecture," which organically combines elements of various cultural traditions with innovative technological solutions. This phenomenon is becoming increasingly relevant in the modern world, where architects strive to find a balance between traditional values and contemporary demands. Based on the analysis of international experience and specific examples, successful strategies for integrating local features into the contemporary architectural context are demonstrated. The research emphasizes the importance of a balanced approach to design that considers both global sustainability trends and the need to preserve cultural heritage. An important aspect is also the role of architects in shaping an environment that reflects the uniqueness of local cultures while meeting modern requirements. The analysis conducted in the article provides a foundation for further development of methodological approaches regarding the harmonious combination of local identity with global standards in architectural practice. The article highlights current problems and offers Ukrainian specialists practical recommendations for further research on the topic of "hybrid architecture" in order to create a theoretical basis for the implementation of successful hybrid solutions in the Ukrainian architectural and urban planning context. This research can serve as a valuable resource for architects and designers seeking to create spaces that reflect cultural specificity while meeting contemporary demands, as well as for specialists in urban studies and cultural studies interested in integrating traditional values into modern projects.